Impact of public sector governance and human capital development on Myanmar's economic growth - Asada, Hidekatsu (Economic Journal of Emerging Markets, 2024)
Purpose ─ This research examines the effects of Myanmar's domestic economic reform measures on its economic growth, highlighting the impact of public sector governance and human capital development. Methods ─ The Toda-Yamamoto test on Granger causality and the vector error correction model are employed to examine the impact of Myanmar's domestic economic reform measures on its economic growth.Finding ─ The results reveal that unidirectional causality existed, from public sector governance to economic growth and human capital development to economic growth. The vector error correction model revealed that public sector governance and human capital development had a long-term and positive relationship with economic growth from 2001 to 2019.Implication ─ The study confirms that Myanmar's domestic economic reform measures contributed to its economic growth from 2001- 2019. These findings underpin the importance of continuing domestic economic reform, such as public sector governance and promoting human capital development, to achieve economic growth in the long run. Originality ─ This paper contributes to existing literature by shedding light on the impact of public sector governance, human capital development, and public sector governance on Myanmar's economic growth.